And they were wonderful teachers : Florida's purge of gay and lesbian teachers - Graves, Karen, 1959- (Book collections on Project MUSE., 2009)
Focusing on Florida's purge of gay and lesbian teachers from 1956 to 1965, this study explores how the Florida Legislative Investigation Committee, commonly known as the Johns Committee, investigated and discharged dozens of teachers on the basis of sexuality. Details how teachers were targeted, interrogated, and stripped of their professional credentials, and examines the extent to which these teachers resisted the invasion of their personal lives. Contrasts the experience of three groups--civil rights activists, gay and lesbian teachers, and University of South Florida personnel--called before the committee and looks at the range of response and resistance to the investigations. Highlights the importance of sexuality in American and education history and argues that Florida's attempt to govern sexuality in schools implies that educators are distinctly positioned to transform dominant ideology in American society. From publisher description.